BIOTYPE EXPRESSION AND INSECTICIDE RESPONSE OF Bemisia tabaci CHEMOSENSORY PROTEIN‐1. Issue 3 (29th January 2014) - Liu, Guo Xia; Xuan, Ning; Chu, Dong; Xie, Hong Yan; Fan, Zhong Xue; Bi, Yu Ping; Picimbon, Jean‐François; Qin, Yu Chuan; Zhong, Su Ting; Fa Li, Yao; Gao, Zhan Lin; Pan, Wen Liang; et al.
<x xml:space="preserve">Abstract</x> Chemosensory proteins (CSPs) are a group of small soluble proteins found so far exclusively in arthropod species. These proteins act in chemical communication and perception. In this study, a gene encoding the Type 1 CSP (BtabCSP1) from the agricultural pest Bemisia tabaci (whitefly) was analyzed to understand sequence variation and expression specificity in different biotypes. Sequence analysis of BtabCSP1 showed significant differences between the two genetically characterized biotypes, B and Q. The B‐biotype had a larger number of BtabCSP1 mutations than the Q‐biotype. Similar to most other CSPs, BtabCSP1 was more expressed in the head than in the rest of the body. One‐step RT‐PCR and qPCR analysis on total messenger RNA showed that biotype‐Q had higher BtabCSP1 expression levels than biotype‐B. Females from a mixed field‐population had high levels of BtabCSP1 expression. The interaction of BtabCSP1 with the insecticide thiamethoxam was investigated by analyzing the BtabCSP1 expression levels following exposure to the neonicotinoid, thiamethoxam, in a time/dose‐response study. Insecticide exposure increased BtabCSP1 expression (up to tenfold) at 4 and 24 h following 50 or 100 <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4srhdpkf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>g/ml treatments.